Exploring Teacher Expectations and Experiences in the Preschool-Primary School Transition Process - Robayanti, Dinda; Djoehaeni, Heny (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
This research explored the expectations, experiences, and challenges felt by Preschool and Primary school teachers. The expectations, experiences, and challenges teachers face can be considered for policy direction, implementation guidelines, and developing transitional preschool learning methods more contextual to real-world conditions and needs. The participants in this study include three lower primary school teachers and two Grade B kindergarten teachers. The research approach used is qualitative-descriptive. The research findings indicate that teachers have expectations that the preschool-primary school transition process is not solely the responsibility of preschool or primary school teachers. Still, there should be continuity and a shared perception between preschool and primary school teachers to ensure a seamless transition process. The experiences and challenges teachers face in teaching children during the transition period include dealing with students with different characteristics, which requires teachers to analyse each student's specific needs, especially when they encounter difficulties during this transition